Acute Changes on Pulmonary Pressure Following Percutaneous Secundum Atrial Septal Defect Closure - Wiryanto J., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Acute Changes on Pulmonary Pressure Following Percutaneous Secundum Atrial Septal Defect Closure